(untitled) (Asian Journal of Plant Biology, 2014)
The advancement in genomics technology has produced vast amount of expressed sequence tags (ESTs) sequence from tropical fruits. These resources have increased the public availability of ESTs sequence from year after year. Therefore, this effort permits mining of single nucleotide polymorphism (SNP) and simple sequence repeat (SSR) from EST tropical fruits. SNP and SSR are types of molecular marker which commonly used in modern genetic analysis for wide application such as diversity analysis, linkage analysis and association study. In this study, a small scale EST sequences from tropical fruits (pineapple, mango, coconut and banana) were retrieved from dbEST database (www.ncbi.nlm.nih.gov/dbEST/ ) as of March 2013. Various bioinformatics tools were applied for rapid discovery of SNP and SSR marker from EST sequences. We analyzed 31,920 unigenes (contigs and singletons) representing a total of 77,418 ESTs from four tropical fruits for their potential use in developing SNP and SSR markers. A total of 13,709 EST-SNP were discovered while a total of 4853 EST-SSR were discovered from these four tropical fruits. The most abundant EST-SSR repeat is from trinucleotide (15,957 repeats) followed by dinucleotide (13,797 repeats) and tetranucleotide (973 repeats). Here, 1738 primers from SNP while 2033 primers from SSR were passed through the setting criteria and were selected for validation using genotyping platform. This study not only serves as a resource for marker development in tropical fruits but can provide a better insight into the selection of candidate genes of interest.